Hybrid improper ferroelectricity in a Si-compatible CeO2/HfO2 artificial superlattice - Pawan Kumar; Jun Hee Lee (npj Computational Materials)
Abstract Hybrid improper ferroelectrics (HIFs), characterized by ferroelectric polarization arising from the rotation of two symmetry inequivalent antiferrodistortive modes, exhibit exotic properties such as T-independent dielectric constants and robustness against depolarizing field. Here, using first-principles simulations, we report a new $$P{2}_{1}$$ P 2 1 phase in a Si-compatible CeO2/HfO2 superlattice that exhibits remarkably robust hybrid improper ferroelectricity, induced by the in-plane oxygen rotations of two antiferrodistortive distortion modes. These non-polar distortions are coupled with a polar distortion through a trilinear coupling in the superlattice, stabilizing ferroelectricity as the competing ground state with the assistance of epitaxial strain. The estimated out-of-plane polarization ( $$P=30.3\,μ C/cm^{2}$$ P = 30.3 μ C / c m 2 ) is switchable with a remarkably small energy barrier of 8.5 meV/atom and relatively smaller coercive field relative to bulk HfO2, expected to reduce the operational voltage of ferroelectric devices. Our discovery may offer unexpected opportunities for innovating high-performance, low-voltage devices, and promising advancements in next-generation CMOS compatible oxide-based electronics.